Using the RECORD guidelines to improve transparent reporting of studies based on routinely collected data - Harron, Katie; Benchimol, Eric; Langan, Sinead (International Journal of Population Data Science, 2018)
Transparent reporting of routinely-collected data studies is key to producing valid and reliable research that can inform decisions about patient care and health systems. This article discusses some of the unique challenges in using these data sources, and explains how the REporting of studies Conducted using Observational Routinely-collected Data (RECORD) guidelines were developed to help researchers and journals to maintain a high level of quality in reporting of healthcare studies using routinely-collected data.